2020
DOI: 10.1007/978-1-0716-0997-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Mitochondrial Genome in Plant Taxonomic Studies

Abstract: Size, structure and sequence content lability of plant mitochondrial genome (mtDNA) across species has sharply limited its use in taxonomic studies. Historically, mtDNA variation has been first investigated with RFLPs, while the development of universal primers then allowed studying sequence polymorphisms within short genomic regions (< 3 kb). The recent advent of NGS technologies now offers new opportunities by greatly facilitating the assembly of longer mtDNA regions, and even full mitogenomes.Phylogenetic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…Complete organellar genomes have been used as foundational markers in understanding phylogenetic relationships between species [ 3 , 23 , 24 ]. In our study, we concatenated all shared coding genes from each organelle genome and used these matrices to infer phylogenetic trees from chloroplast and mitochondrial data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Complete organellar genomes have been used as foundational markers in understanding phylogenetic relationships between species [ 3 , 23 , 24 ]. In our study, we concatenated all shared coding genes from each organelle genome and used these matrices to infer phylogenetic trees from chloroplast and mitochondrial data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The diameter of each haplotype is proportional to its frequency in the dataset. reference data and rates (Gilbert et al, 2008;Singh et al, 2009;Duminil and Besnard, 2021;Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial sequence data had not been utilized well in angiosperm phylogeny compared to plastid data over several decades [40]. However, in recent years, a growing number of studies showed the potential usefulness of mitochondrial data for phylogenetic analysis [20,21,[41][42][43][44][45]. The whole mitogenome can show a level of informative characters equivalent to (or higher than) the whole plastome, due to the overwhelming total length at a species-level taxonomy [43,45].…”
Section: Introductionmentioning
confidence: 99%